2015
DOI: 10.1146/annurev-economics-080614-115445
|View full text |Cite
|
Sign up to set email alerts
|

Affirmative Action in Undergraduate Education

Abstract: The use of race in college admissions is one of the most contentious issues in U.S. higher education. We survey the literature on the impact of racial preferences in college admissions on both minority and majority students. With regard to minority students, particular attention is paid to the scope of preferences as well as how preferences affect graduation, choice of major, and labor market earnings. We also examine how schools respond to bans on racial preferences and the effects these responses have on rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 69 publications
(62 reference statements)
0
24
0
Order By: Relevance
“…A useful review of current affirmative action in college admissions research can be found in Arcidiacono et al . (). In states where affirmative action has been banned as a result of these legal challenges researchers have found large decreases in minority enrolments at selective universities (Kain et al ., ; Arcidiacono et al ., ), although there is some evidence that targeted recruitment programmes can offset these effects (Andrews et al ., ).…”
Section: Research On Affirmative Actionmentioning
confidence: 99%
“…A useful review of current affirmative action in college admissions research can be found in Arcidiacono et al . (). In states where affirmative action has been banned as a result of these legal challenges researchers have found large decreases in minority enrolments at selective universities (Kain et al ., ; Arcidiacono et al ., ), although there is some evidence that targeted recruitment programmes can offset these effects (Andrews et al ., ).…”
Section: Research On Affirmative Actionmentioning
confidence: 99%
“…Despite their widespread use, however, we actually know very little about how members of the general public feel toward some of the most commonly adopted diversity policies. While the public opinion literature has devoted significant attention towards individuals' attitudes on affirmative action 1 in the U.S. (see Arcidiacono, Lovenheim, and Zhu, 2015;Crosby, Iyer, and Sincharoen, 2006;Harper and Reskin, 2005;Krysan, 2000;and Sears, Sidanius, and Bobo, 2000 for reviews), few workplaces use the language of affirmative action to describe their workplace policies (Bielby, 2000). Furthermore, although there are many different types of workplace diversity policies used today, the vast majority of them do not fit the prototypical and controversial preferential hiring programs that people may think of when they are asked about affirmative action (Bielby, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This article examines a number of issues but frames much of the discussion around the "minority mismatch hypothesis," an important part of the affirmative action debate but a separate question from the issue of segregation across colleges that I study here. See Arcidiacono et al (2015) for an additional review of affirmative action research. 3 The means employed must also be "narrowly tailored" to achieve the benefits of diversity.…”
Section: Introductionmentioning
confidence: 99%